Picosecond photoluminescence measurements of Landau level lifetimes and time dependent Landau level linebroadening in modulation-doped GaAs-GaAlAs multiple quantum wells - Ryan, J; Taylor, R; Turberfield, A; Worlock, J (1985)
We report the first picosecond time-resolved photoluminescence measurementsof hot-carrier relaxation in a modulation-doped GaAs-GaAlAs MQW in the presence of strong magnetic fields. We have measured the lifetimes of carriers in excited Landau levels and have determined the time-dependent carrier temperature. We find that the cooling rate is slower in applied field tthan at B=0; also there is a significant increase in the cooling rate for B {greater-than or approximate} 10T. We report also the observation of highly time-dependent linewidths of the Landau levels. © 1985.